Online Shopping Intention and Behavior of Customers: Study of the Extended Unified Theory of Acceptance and Use of Technology, Trust and Long Tail Effect - Ha, Nguyen Thu; Long, Tran Trong Vu; Thuy, Pham Thanh; Anh, Le Thi Tu (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 1, 2019)
Along with the popularity of Internet as well as information and communication technology, online shopping is gradually becoming an alternative to traditional shopping form. Based on the Extended Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), this paper proposes a framework utilizing 9 factors (performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value and habit, trust, and the long tail effect) to analyze customer’s intention and behavior of online shopping. This analytical framework could be used in future studies on customer’s behavior of shopping through websites of e-commerce in Vietnam.